LAW OF TALAQ UNDER MUSLIM PERSONAL LAW IN INDIA AND RECENT DEVELOPMENTS (A PILOT STUDY) - Dr. Meena Kumari (Sampreshan, ISSN:2347-2979 UGC CARE Group 1, 2025)
This study aims to review the prevailing practice of talaq and how deep the gap exists between theory and practice, which may lead to exploring the elements of deterrence on the unilateral ability of a Muslim man to utter talaq, its structures, and perception of Muslim women. The goal is to describe the view and perspective exhaustively as to how Muslim women feel their opinion about the practice of talaq, which is discriminatory towards women, and what to do to endorse gender equality and progressive treatment.